2014
DOI: 10.1186/1472-6831-14-72
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of lifestyle change plus dental care (LCDC) program on improving glycemic and periodontal status in the elderly with type 2 diabetes

Abstract: BackgroundCurrently, there is an increased prevalence of diabetes mellitus among the elderly. To minimize adverse effects on glycemic control, prevention and management of general and oral complications in diabetic patients is essential. The purpose of the present study is to assess the effectiveness of a Lifestyle Change plus Dental Care (LCDC) program to improve glycemic and periodontal status in the elderly with type 2 diabetes.MethodsA quasi-experimental study was conducted in Health Centers 54 (interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 22 publications
(33 reference statements)
8
38
0
2
Order By: Relevance
“…As one goal for periodontal treatment BOP elimination, the decline in the BOP values for the intervention group from 26.2% to 13.7% can be considered clinically significant. In other studies that informed patients with type 2 diabetes about how to brush their teeth more effectively and provided instruction about oral hygiene, the intervention groups showed significant improvements in BOP, which concurs with the current study's results. However, there was no significant change in the intervention group in relation to PPD, which is associated with plaque accumulation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As one goal for periodontal treatment BOP elimination, the decline in the BOP values for the intervention group from 26.2% to 13.7% can be considered clinically significant. In other studies that informed patients with type 2 diabetes about how to brush their teeth more effectively and provided instruction about oral hygiene, the intervention groups showed significant improvements in BOP, which concurs with the current study's results. However, there was no significant change in the intervention group in relation to PPD, which is associated with plaque accumulation.…”
Section: Discussionsupporting
confidence: 91%
“…However, improvements were not observed in relation to increased PPD, which is a chronic, long‐term condition that worsens with an infection, or chronic inflammation, which was assessed by examining TNF‐α levels. Moreover, reports from studies that investigated the treatment of periodontal disease in diabetic patients have described improvements in HbA1c levels and periodontal disease; similar improvements were seen in studies that educated patients about how to care for periodontal disease and diabetes simultaneously . On the other hand, studies like the current study, which only provided education related to caring for periodontal disease, have demonstrated improvements in periodontal disease, but no significant improvements in HbA1c levels.…”
Section: Discussionsupporting
confidence: 68%
“…The LCDC program 20 is based on the health‐belief model, social cognitive theory, and cognitive–behavioral theory. The LCDC program used the common risk factor approach, 16 which integrated DM and periodontal disease prevention by LCDC using multiple professionals, including a doctor, two nurse practitioners, two dentists, and two dental assistants.…”
Section: Methodsmentioning
confidence: 99%
“…Kvalitet života može se definisati kao stepen do koga neka jedinka može da uživa u svakodnevnim životnim aktivnostima, kao i da na njih utiče na direktan ili indirektan način. Kvalitet života u starosti zavisi i od toga koliko su problemi koje ima stara osoba sa jednom ili više sistemskih oboljenja sanirani [5][6][7][8].…”
Section: Starost I Starenjeunclassified